Synthesis, Molecular Docking Studies, and Anticonvulsant Evaluation of Novel bis‐Phenylhydrazones against Chemically induced Seizures in Mice. Issue 8 (16th June 2017) - Siddiqi, Humaira Masood; Tabasum, Aneela; Qasim, Sumera; Akhtar, Muhammad Shoaib; Kalsoom, Saima; Ansari, Farzana Latif
Abstract : A series of novel bis‐phenylhydrazones were synthesized by the condensation of dialdehydes with phenylhydrazine to evaluate them for their anticonvulsant activity. Efficacy of newly synthesized compounds against pentylenetetrazole (PTZ)‐induced, strychnine‐induced, and picrotoxin‐induced convulsions was tested after administration of these compounds to albino mice via the oral route. All the five tested compounds showed anticonvulsant activity against strychnine‐induced and picrotoxin‐induced convulsions in a dose‐dependent manner. However, the effect was more significant against PTZ‐induced convulsions. Behavioral pattern studies on mice suggested that these compounds are less neurotoxic compared to phenytoin. Molecular docking studies were carried out to correlate the experimental and theoretical results. It was concluded that these compounds exerted their anticonvulsant effect through the modification of the function of GABA receptor‐mediated chloride channels. Molecular docking studies revealed a good correlation, which indicated that in silico studies could provide an alternate tool for the identification and design of more potent anticonvulsant agents. Abstract : A series of novel bis ‐phenylhydrazones was synthesized. Anticonvulsant behavior of newly synthesized compounds were tested after administration of these compounds to albino mice via oral route. All the five test compounds showed anticonvulsant activity. Molecular docking studies were carried out to correlate experimental and theoretical results. These studies revealed a good correlation between experimental and docking results.